Carbonation of municipal solid waste gasification fly ash: effects of pre-washing and treatment period on carbon capture and heavy metal immobilization - Qin, Junde (2022)
Carbon capture has become an important technology to mitigate ever-increasing CO2 emissions worldwide, and alkali waste is a potential source of CO2 capture material. Slagging-gasification is a novel technology for treating municipal solid waste (MSW), and the gasification fly ash (GFA) is the only solid residue that is not reused at present due to its high heavy metal content. GFA contains high amounts of Ca(OH)2 and Ca(OH)Cl, making it protentional for CO2 capture. In this study, GFA and washed gasification fly ash (WGFA) were treated with CO2 for different treatment periods. Weight changes of samples were recorded to evaluate the efficiency of CO2 capture. To assess the properties of treated GFA, pH value, leached heavy metal concentration, mineral composition, and microscopic morphology were studied. The results revealed that GFA and WGFA could adsorb 18.8% and 23.7% CO2 of their weights, respectively. Carbonation could immobilize heavy metals including Pb, Zn, and Cu when a proper treatment period was applied. An excessive treatment period decreased the efficiency of heavy metal immobilization. Pre-washing is recommended as a pre-treatment method for GFA carbonation, which increased the efficiency to adsorb CO2, improved the pH of carbonated GFA, and enhanced the effect to immobilize heavy metals.